PEMANFAATAN RUANG VERTIKAL PADA AKTIVITAS HARIAN ORANGUTAN (Pongo pygmaeus wurmbii) DI STASIUN RISET CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG, KALIMANTAN BARAT - Awit Mulyawarman; Tri Rima Setyawati; Riyandi Riyandi (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Orangutans are solitary animals from the Pongidae family. There are three sub-species of Bornean orangutans, i.e. Pongo pygmaeus wurmbii, P. pygmaeus pygmaeus and P. pygmaeus morio, all of which are highly endangered. Orangutans carry out several daily activities such as eating, moving, resting, and nesting in the tree canopy. However, it has yet remains unknown on how their behaviours vary with tree height. This study aimed to determine the frequency of presence, daily activities of orangutans, and vertical space utilization in orangutan activities in the natural habitat of the Panti Branch Research Station, Gunung Palung National Park. This study used the Focal Animal Sampling method with a two minute time interval for ± 12 hours and was studied for over six months. The focal orangutans whose activities were recorded during the study consisted of 12 individuals divided into 3 age groups, namely the adult, adolescent, and juvenile age groups. The results showed that the daily activity of orangutan was observed on 36 species of trees with the greatest frequency found on Garcinia sp. and Syzigium sp. accounted for33% each. The female orangutans were found to be more dominant in feeding activities (3.93 per day), while male orangutans spent more time for resting activities (4.56 hours per day). The utilization of vertical space in young male orangutans took place in tall trees and eating activities occurred at an altitude of 33.6 m. On average, teenage female orangutans choose tree to make their nests in trees 30 m high.